2008
DOI: 10.1002/per.671
|View full text |Cite
|
Sign up to set email alerts
|

Moderating effects of personality on the genetic and environmental influences of school grades helps to explain sex differences in scholastic achievement

Abstract: Girls consistently achieve higher grades than boys despite scoring lower on major standardized tests and not having higher IQs. Sex differences in non-cognitive variables such as personality might help to account for sex differences in grades. Utilizing a large sample of 17 year-old twins participating in the Minnesota Twin Family Study (MTFS), we examined the roles of Achievement Striving, SelfControl, and Aggression on sex differences in grade point average (GPA). Each personality trait was a significant pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 51 publications
0
22
1
Order By: Relevance
“…Each of these personality traits was a significant predictor of GPA, with sex differences in aggression accounting for one-half of the gender differences in GPA. The finding of the present study about the mediation effect of student engagement provides additional empirical support to the claim of many researchers that gender differences in school performance lie in personality and motivation factors instead of cognitive factors (e.g., Freudenthaler et al, 2008;Hicks et al, 2008;Johnson, 2008;Ruban & McCoach, 2005). However, it is noteworthy that the mediation effect of student engagement on the association between gender and academic performance was small in the present study with a large sample size.…”
Section: Findings Relative To Previous Studiescontrasting
confidence: 35%
See 2 more Smart Citations
“…Each of these personality traits was a significant predictor of GPA, with sex differences in aggression accounting for one-half of the gender differences in GPA. The finding of the present study about the mediation effect of student engagement provides additional empirical support to the claim of many researchers that gender differences in school performance lie in personality and motivation factors instead of cognitive factors (e.g., Freudenthaler et al, 2008;Hicks et al, 2008;Johnson, 2008;Ruban & McCoach, 2005). However, it is noteworthy that the mediation effect of student engagement on the association between gender and academic performance was small in the present study with a large sample size.…”
Section: Findings Relative To Previous Studiescontrasting
confidence: 35%
“…Although no previous studies have investigated the role of student engagement in the achievement gender gap, herein, the finding that student engagement mediated the association between gender and academic performance is in line with those of previous studies that investigated the role of personality and motivation factors in gender differences in school achievement. For instance, Hicks et al (2008) found that achievement striving, self-control, and aggression accounted for gender differences in grade point average (GPA). Each of these personality traits was a significant predictor of GPA, with sex differences in aggression accounting for one-half of the gender differences in GPA.…”
Section: Findings Relative To Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetically sensitive studies have largely focused on intelligence, consistently showing that the phenotypic correlation between intelligence and educational achievement is mediated genetically to a substantial extent (43)(44)(45)(46)(47)(48)(49)(50). Only a handful of studies have considered genetic contributions to educational achievement from other traits in addition to intelligence, such as self-efficacy (51), motivation (52,53), personality (54), behavior problems (55)(56)(57)(58), and perceptions of home environment (59) and school environment (60). Because these behavioral traits are correlated with each other and with educational achievement, adding up their separate genetic contributions to educational achievement could exceed the heritability of educational achievement.…”
Section: Significancementioning
confidence: 99%
“…Girls and boys with higher scores for hostile sexism who were also more aggressive were at a higher risk of experiencing problems with their academic achievement. Externalizing behaviour problems was negatively related to poor academic achievement [13,67]. Although there were not significant differences in the studied model according to sex, this is where males may be more disadvantaged than females, given their higher scores in hostile sexism and aggressiveness.…”
Section: Discussionmentioning
confidence: 76%